THE YEAR 2025 IN UZBEKISTAN IS THE YEAR OF ENVIRONMENTAL PROTECTION AND THE "GREEN" ECONOMY: https://doi.org/10.5281/zenodo.15869502 - Vashko , Irina; Mansurov , Shahzod (Journal of Contemporary World Studies, 2024)
By 2025, the world will increasingly focus on adapting to changing climatic conditions and protecting the environment. Significant progress is expected this year in the field of environmental protection and the development of a green economy. This article examines environmental news and economic changes in 2025. Uzbekistan has taken significant steps in recent years to promote environmental protection and the development of a green economy. A green economy means not only efficient use of natural resources, but also combating climate change, reducing waste and recycling it. Uzbekistan’s transition to a "green" economy is aimed at sustainable development and environmental stability and includes various initiatives.